2018
DOI: 10.1634/theoncologist.2018-0317
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Clinician Discordance in Perceptions of Treatment Risks and Benefits in Older Patients with Acute Myeloid Leukemia

Abstract: Older patients with acute myeloid leukemia (AML) are confronted with challenging decisions regarding treatment with "intensive" chemotherapy that carries significant toxicity for a small chance of a cure versus "nonintensive" chemotherapy to control the disease, but with fewer side effects. A clear understanding of the likely outcome and risks of the various treatment strategies is essential for these patients to make informed decisions about their care. This article reports that older patients with AML overes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 41 publications
0
44
2
Order By: Relevance
“…2 In another study of 100 older patients with acute myeloid leukemia, patients who reported a lower likelihood of cure compared with their hematologists were more likely to report greater depressive symptoms. 3 The difference in findings among these studies compared with those of the current study may reflect the heterogeneity of study populations and varying follow-up periods. Therefore, the relationships between psychological health and prognostic understanding need to be evaluated further in future studies.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…2 In another study of 100 older patients with acute myeloid leukemia, patients who reported a lower likelihood of cure compared with their hematologists were more likely to report greater depressive symptoms. 3 The difference in findings among these studies compared with those of the current study may reflect the heterogeneity of study populations and varying follow-up periods. Therefore, the relationships between psychological health and prognostic understanding need to be evaluated further in future studies.…”
Section: Discussioncontrasting
confidence: 56%
“…Prior studies have demonstrated that up to 82% of patients with hematologic malignancies have a different understanding of their prognosis compared with their hematologist. [2][3][4][5] The majority of this discordance is skewed toward optimism, whereby patients tend to have higher expectations for cure. Discordance may exist due to patient-related (eg, beliefs, emotional distress, social support), physician-related (eg, communication, reluctance Cancer March 15, 2020 in discussing prognosis), and societal factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who believe their prognosis is more favorable are more likely to pursue aggressive treatment . The majority of patients tend to overestimate their chance of cure, both for AML and other types of cancer …”
Section: Discussionmentioning
confidence: 99%
“…Although the acuity of an AML diagnosis can be overwhelming for patients, a majority want to be involved in the decision-making process regarding treatment options. [35][36][37][38] Patients who believe their prognosis is more favorable are more likely to pursue aggressive treatment. 37 The majority of patients tend to overestimate their chance of cure, both for AML and other types of cancer.…”
Section: Discussionmentioning
confidence: 99%